O romanesco da discordância em António Lobo Antunes - Stefanello, Camila (2021)
The literary project by António Lobo Antunes, since the beginning of his fictional production, points, even though in different nuances, to a break with the limits of a linear and purely chronological articulation of temporality, opening, thus, to an exploration of the time of the characters’ minds. New and singular implications derive from this, not only for the formal management of the intrigue, but also for the constitution of the identity of the characters that inhabit this fictional universe. The doctoral thesis entitled “The romanesque of disagreement in António Lobo Antunes” investigates the manifestations of the philosophical concept of disagreement, postulated by Paul Ricoeur, in two novels by the Portuguese writer, namely, What are those horses that make shadow on the sea?, published in 2009, and To be midnight it is not enough want to be it, published in 2012. For this, we analyze, in both narratives, the fictional experience of time lived by the characters, which annihilates the agreement that cannot be re-established in the incomplete, chaotic and fragmented narrative act of the intrigue by Lobo Antunes. In this sense, based on the comprehension of temporality as aporetic and distended and of its implications for the discordant nature of the intrigue, we also investigates the problematic of constitution of a narrative identity. This because, in the process of constitution of identity, it is found implicated the potentiality of unit and of narrative totality of a life, considering that the narrative identity results of the dialectical relation between disagreement (the plurality of experienced events) and the agreement (the totalizing and cohesive articulation of these events). For this investigation, we use as theoretical referential, mainly, the work by Paul Ricoeur about the triad narrative, temporality and narrative identity. Thus, this thesis intends to identify, more than evincing formally the implications of the concept of disagreement in the novels by António Lobo Antunes, which is the conception of world and subject privileged by the narratives of the author, especially in his last phase of production.